The Proximities of Asteroids and Critical Points of the Distance Function - Milisavljevic, S. (Serbian Astronomical Journal, 2010)
The proximities are important for different purposes,for example to evaluate the risk of collisions of asteroids or comets with the Solar-System planets. We describe a simple and efficient method for finding the asteroid proximities in the case of elliptical orbits with a common focus. In several examples we have compared our method with the recent excellent algebraic and polynomial solutions of Gronchi (2002, 2005).